ANALYSIS OF THE EFFECT OF WATER, SANITATION, AND HYGIENE (WASH) ON DIARRHEA CASES AMONG TODDLERS IN SOUTH CIMAHI DISTRICT - Nadifa, Syahla
Mothers play a crucial role in maintaining the health of children, especially during the toddler years. Diarrhea is a frequently occurring illness among toddlers and can lead to fatalities if not properly managed. Environmental and behavioral factors are the primary causes of diarrhea, with personal hygiene being a significant factor. The research methodology employed in this study is observational research using a structured questionnaire. The study participants consist of mothers of toddlers in the South Cimahi District. The collected data includes information about the mothers' environmental conditions and personal hygiene, as well as the cases of diarrhea experienced by their toddlers. The research approach utilized in this study is a Cross-Sectional Study, conducted to examine the dynamic correlation between risk factors and the approach process. The bivariate analysis employed is the Chi-Square test. In determining the variables that act as risk factors, the Prevalence Ratio (PR) value is used, which represents the prevalence ratio between the exposed group and the non-exposed group. The research findings indicate that variables such as access to clean water and drinking water do not pose a risk factor for diarrhea and lack significant correlation. However, other variables such as personal hygiene show a significant relationship with diarrhea (p=0.082), ownership of a squat toilet (p=0.024), ownership of a septic tank (p=0.037), and waste management practices (p=0.077). On the other hand, there are several variables that act as risk factors for diarrhea, including personal hygiene (PR=1.820), quality of clean water (PR=1.042), quantity of clean water (PR=1.403), continuity of clean water (PR=2.100), type of toilet flooring (PR=2.223), ownership of a septic tank (PR=2.907), and waste management practices (PR=1.961). Therefore, it is essential to enhance sanitation and hygiene access across the entire community to prevent the spread of diseases throughout the South Cimahi District area.